E-Assessment for Characters Independence - Asrial, Asrial; Syahrial, Syahrial; Maison, Maison; Muhaimin, Muhaimin; Kurniawan, Dwi Agus (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This study aims to apply E-assessment and evaluation of the character of student learning independence. E-Assessment and evaluation of student learning independence in this study to see the character of student learning independence in science subjects and how the teacher responds to the development of E-Assessment and evaluation of student learning independence with the MySQL system. This research method uses 3 stages, namely: (1) Development, (2) Implementation, and (3) Evaluation carried out on respondents totaling 529 students and 14 teachers in Jambi Province of Indonesia. The results of this study are the validator gives good results regarding the assessment of e-independence characters in the category given is very feasible and obtained valid statements of 24 statements with a reliability value of 0.870. Indicate that the character of student learning independence in learning is classified as good 65.8% (348 students of 529 students) and teacher responses are classified as good with 57% (8 teachers of 14 teachers). So it was concluded that the E-Assessment received a good response and needed to be developed on a large scale.